Influence of Ash and Coconut Shell Against Compressive Strength and Permeability Characteristics of Pervious Concrete - et.al, Suwendy Arifin (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Pervious concrete or non-fine concrete is a simple form of lightweight concrete made by eliminating the use of fine aggregates. As a result of not using fine aggregate in pervious concrete, then created a cavity filled with air and water can be passed. This cavity resulted in reduced density of the concrete as well as the reduced amount of area that needs to be covered by cement paste, thereby reducing the compressive strength. To increase the compressive strength of pervious concrete, in this study will utilize waste material. The waste material is the cocnut shell ash and coconut shell to strengthen the coarse aggregate bonds, so it is expected to increase the compressive strength along with the increase in permeability. Thus, in this study will replace part of the coarse aggregate with coconut shell with percentage 0%, 2,5%, 5%, 7,5%, 10% and partially replace cement with coconut shell ash with percentage 0%, 2,5%, 5%, 7,5%